The association of overweight and ankle injuries in children. - Zonfrillo, Mark R; Seiden, Jeffrey A; House, Ellen M; Shapiro, Eugene D; Dubrow, Robert; Baker, M Douglas; Spiro, David M (Ambulatory pediatrics : the official journal of the Ambulatory Pediatric Association, 2008)
Overweight children are at increased risk for many medical problems. Trauma is the leading etiology of childhood morbidity and mortality. No previous study has evaluated the association between overweight and acute ankle injuries in children. We hypothesized that being overweight is associated with an increased risk of ankle injury in children.
Keywords: Adolescent; Ankle Injuries; Body Mass Index; Case-Control Studies; Child; Female; Humans; Male; Odds Ratio; Overweight; Risk